2009
DOI: 10.1111/j.1365-2354.2009.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased tryptophan degradation in patients with bronchus carcinoma

Abstract: Expression of tryptophan-degrading enzyme indoleamine (2,3)-dioxygenase in tumour tissue is proposed to represent an important tumour immunoescape mechanism. To further investigate the potential role of activated indoleamine (2,3)-dioxygenase in bronchus carcinoma, we examined serum tryptophan and kynurenine concentrations in nine patients with small cell lung cancer and in 27 patients with non-small cell lung cancer. Tryptophan metabolic changes were compared with markers of inflammation and immune activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
4
17
0
2
Order By: Relevance
“…We found that IDO activity was higher in cancer patients than in healthy individuals, consistent with previous observations in lung cancer, 24,25,31 bladder cancer, hepatocellular carcinoma, renal cell Fischer's exact p = 0.0003). This difference may reflect a posttranscriptional regulation of IDO.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We found that IDO activity was higher in cancer patients than in healthy individuals, consistent with previous observations in lung cancer, 24,25,31 bladder cancer, hepatocellular carcinoma, renal cell Fischer's exact p = 0.0003). This difference may reflect a posttranscriptional regulation of IDO.…”
Section: Discussionsupporting
confidence: 81%
“…24,25 This said, how IDO activity changes of rapamycin (mTOR) and protein kinase C Θ (PKCΘ), thereby inhibiting autophagy. 8 In fact, IDO is overexpressed by many human cancers 9 and may serve as an escape mechanism from host immunity.…”
Section: Introductionmentioning
confidence: 99%
“…IDO activity is associated with tumor induction and is often highly expressed in solid tumors (Munn & Mellor, 2013). Higher kynurenine/tryptophan ratios and lower tryptophan concentrations in blood compared to healthy controls have been reported in colorectal cancer, malignant melanoma, non-small cell and small cell lung cancer, ovarian cancer, endometrial cancer, vulvar cancer, and breast cancer patients (de Jong et al, 2011; Engin et al, 2010; Huang et al, 2002; Lyon et al, 2011; Sperner-Unterweger et al, 2011; Suzuki et al, 2010; Weinlich et al, 2007), although the opposite pattern was noted in a study of primary cervical cancer patients (Fotopoulou et al, 2011). Thus, it appears that increased IDO activity in peripheral blood is associated with many malignancies prior to treatment.…”
Section: Cancer Patients Prior To Treatmentmentioning
confidence: 89%
“…The key enzymes in degradation of tryptophan through the kynurenine pathway, IDO and TDO, as well as downstream catabolites may influence the immune system (11,24), and thus affect cancer development and progression (7,8,10,12,17,18,25). KTR is considered an indirect marker of IDO activity and was in the current study associated with increased risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The kynurenine pathway ( Fig. 1), and in particular, the key enzymes involved, 2,3-dioxygenase (IDO) and 2,3-tryptophan dioxygenase (TDO), have been implicated in cancer-related immune escape (8,(10)(11)(12)(13). High IDO activity causes an increased conversion of tryptophan to its primary catabolite, kynurenine.…”
Section: Introductionmentioning
confidence: 99%